Przesłanki kształtowania kultury informacyjnej - Łukasik-Makowska, Barbara (Premises of formation of information culture, 2006)
In the article the problem of disproportion between development of infrastructure technology information and communication and personal information culture of users is introduced, which drives to different irregularities and many times blocks efficient usage of technological tools. Advisable formation of information culture should be a duty of all economic subjects. Creating standards of a firm creations and transformations of information inside firms, by building Internet portals favours the development of information culture.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 205-214